Two mitochondrial genomes of freshwater gudgeons in the genus Gobio (Cypriniformes: Gobionidae). Issue 3 (2nd July 2020) - Yi, Tianyu; Fu, Cuizhang
Abstract: Two complete mitochondrial genomes of Gobio acutipinnatus and G. microcephalus are assembled, and they have the same length with slightly high A + T contents (54.88% and 56.57%) in base compositions. Results in the reconstructed phylogeny show that the genus Gobio is a monophyletic group, and it is a sister taxon of the genus Romanogibio .